Peran Partai Politik di Indonesia Dalam Pengembangan Penerapan Hukum Islam - Rahmadani, Nur Fitri; Rahman R, Abd.; R, Rahmatiah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research discusses the role of political parties in Indonesia in the development and implementation of law, with a focus on Islamic-based parties. The main issue raised is how these religious-based parties influence national and regional policies with Sharia principles. The research method used is a qualitative approach with descriptive analytical methods, relying on literature studies and document analysis. The research results show that Islamic political parties play a significant role in legislation, education and the dissemination of Islamic law. Integrate Sharia values in various laws and policies, especially in the Sharia economic sector. Facing challenges by maintaining a balance between the application of Islamic law and the principles of democracy and pluralism.